Halotolerant Marine Rhizosphere-Competent Actinobacteria Promote Salicornia bigelovii Growth and Seed Production Using Seawater Irrigation - Mathew, Betty T.; Torky, Yaser; Amin, Amr; Mourad, Abdel-Hamid I.; Ayyash, Mutamed M.; El-Keblawy, Ali; Hilal-Alnaqbi, Ali; AbuQamar, Synan F.; El-Tarabily, Khaled A. (Frontiers in Microbiology, 2020)
Salicornia bigelovii is a promising halophytic cash crop that grows in seawater of the intertidal zone of the west-north coast of the UAE. This study assess plant growth promoting (PGP) capabilities of halotolerant actinobacteria isolated from rhizosphere of S. bigelovii to be used as biological inoculants on seawater-irrigated S. bigelovii plants. Under laboratory conditions, a total of 39 actinobacterial strains were isolated, of which 22 were tolerant to high salinity (up to 8% w/v NaCl). These strains were further screened for their abilities to colonize S. bigelovii roots in vitro; the most promising ones that produced indole-3-acetic acid, polyamines (PA) or 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (ACCD) were selected for rhizosphere-competency under naturally competitive environment. Three outstanding rhizosphere-competent isolates, Streptomyces chartreusis (Sc), S. tritolerans (St) and S. rochei (Sr) producing auxins, PA and ACCD, respectively, were investigated individually and as consortium (Sc/St/Sr) to determine their effects on the performance of S. bigelovii in the greenhouse. Individual applications of strains on seawater-irrigated plants significantly enhanced shoot and root dry biomass by 32.3-56.5% and 42.3-71.9%, respectively, in comparison to non-inoculated plants (control). In addition, plants individually treated with Sc, St and Sr resulted in 46.1%, 60.0% and 69.1% increase in seed yield, respectively, when compared to control plants. Thus, the synergetic combination of strains had greater effects on S. bigelovii biomass (62.2% and 77.9% increase in shoot and root dry biomass, respectively) and seed yield (79.7% increase), compared to the control treatment. Our results also showed significant (P<0.05) increases in the levels of photosynthetic pigments, endogenous auxins and PA, but a reduction in the levels of ACC in tissues of plants inoculated with Sc/St/Sr. We conclude that the consortium of isolates was the most effective treatment on S. bigelovii growth; thus confirmed by principal component and correlation analyses. To this best of our knowledge, this is the first report about halotolerant rhizosphere-competent PGP actinobacteria thriving in saline soils that can potentially contribute to promoting growth and increasing yield of S. bigelovii. These halotolerant actinobacterial strains could potentially be exploited as biofertilizers to sustain crop production in arid coastal areas.